2021
DOI: 10.3310/hta25030
|View full text |Cite
|
Sign up to set email alerts
|

Lansoprazole for persistent throat symptoms in secondary care: the TOPPITS RCT

Abstract: Background Persistent throat symptoms are commonly attributed to ‘laryngopharyngeal reflux’. Despite a limited evidence base, these symptoms are increasingly being treated in primary care with proton pump inhibitors. Objective To assess the value of proton pump inhibitor therapy in patients with persistent throat symptoms. Design This was a double-blind, plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 120 publications
0
14
0
Order By: Relevance
“… 9 The full trial methodology has been published previously. 10 This study was authorised by the TOPPITS Trials Steering Committee (TSC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 The full trial methodology has been published previously. 10 This study was authorised by the TOPPITS Trials Steering Committee (TSC).…”
Section: Methodsmentioning
confidence: 99%
“…Descriptive statistics for the RSI, CReSS, LPR-HRQL and RFS have been described in full in the TOPPITS trial report. 10 In this analysis, the relationships among the questionnaires and demographic factors (age and BMI) were assessed using the Pearson correlation coefficients—r (total questionnaire scores were normally distributed).…”
Section: Methodsmentioning
confidence: 99%
“…Although many studies have focused on laryngopharyngeal reflux (LPR), laryngitis, asthma, and chronic cough, their results are inconsistent and only a few are randomized controlled trials (RCTs). The few RCTs that have recently been published suggest that PPIs have little or no superiority to placebo in the treatment of extraesophageal GERD symptoms [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent double‐blind, placebo‐controlled trial in patients with persistent throat symptoms, researchers investigated the effectiveness of lansoprazole 30 mg BID for 16 weeks versus placebo and found that in 220 individuals who completed the study, mean RSI scores were not significantly different between the groups, and these results held after 12 months of treatment 27 . Similarly, in the TOPPITS randomized controlled clinical trial, patients with persistent throat symptoms were also randomized to the aforementioned groups and researchers found that in 267 patients completing the primary outcomes, there was no significant difference between RSI scores at 16 weeks or 12 months of follow‐up 28 . Notably, neither of these studies evaluated patients for objective findings of GERD.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…27 Similarly, in the TOPPITS randomized controlled clinical trial, patients with persistent throat symptoms were also randomized to the aforementioned groups and researchers found that in 267 patients completing the primary outcomes, there was no significant difference between RSI scores at 16 weeks or 12 months of follow-up. 28 Notably, neither of these studies evaluated patients for objective findings of GERD. Several reviews and meta-analyses assessing the efficacy of PPIs in patients with suspected LPR have reported mixed results.…”
Section: Proton Pump Inhibitorsmentioning
confidence: 99%